Treatment of Wedge-Shaped Tooth Defect with the Symptom of Hypersensitivity - Hamdi, Musayeva Hanife; Azad, Gurskaya Narmina; Eldar, Karimova Arzu (American Journal of Biology and Natural Sciences, 2025)
A wedge-shaped defect leads to the gradual loss of hard dental tissues and is characterized by pain. Most often, patients complain of pain and an aesthetic defect, both of which negatively affect their psycho-emotional state and quality of life. This issue remains relevant, since the effectiveness of available medications is not always sufficient, or they may be too expensive. Therefore, the search for adequate means and methods of treatment is highly important. In Ufa, wedge-shaped defects and the associated symptom of dental hypersensitivity account for 5.65% and 63.0%, respectively, of the total number of dental patients. Analysis of questionnaires revealed a correlation between sociological parameters (sex, age, profession) and patient quality of life. Positive changes in all clinical manifestations are observed as a result of comprehensive treatment.